A COMPARITIVE STUDY OF SCHOLASTIC ACHIEVEMENT IN MATHEMATICS EXAMINATION IN RELATION TO CONCEPTUAL UNDERSTANDING AND MATHEMATICS ABILITY - Mech, Arundhati; Patra, Kuntala (SCHOOL SCIENCE, 2011)
The study compares two groups of students of Class VII and Class IX, one group belonging to government schools and the other to private schools. Scholastic achievement in examinations was studied in relation to conceptual understanding and mathematics ability. Conceptual understanding and mathematical ability both exhibited positive relationship with scholastic achievements. It was also seen that conceptual understanding and mathematics ability of the students was at a lower level than scholastic achievement. Some common conceptual errors in mathematics were also discussed.